EFFECT OF Nigella sativa AS FEED ADDITIVE ON ORGANOLEPTIC, WATER, PROTEIN, AND CHOLESTEROL CONTENT OF BROILER CHICKEN MEAT WITH HEAT STRESS CONDITION - Vanda, Henni; Nurliana, Nurliana; Sugito, Sugito; Ferasyi, Teuku Reza; Sari, Wahyu Eka; Hanafiah, M.; Akram, Saydul; Daulay, Dina Khairani; Paula, Wita (Jurnal Kedokteran Hewan, 2024)
This study aimed to determine the physical properties, organoleptic, proximate value, and cholesterol level of broiler meat given black cumin (Nigella sativa) as feed supplement and exposed to heat stress. This study used 15-day old chicken (DOC) broilers that were adapted for 14 days and treated on day 15 to day 28. This study used a completely randomised design (CRD) consisting of 5 treatment groups: P0 (commercial feed); P1 (commercial feed + heat stress 34-35 ); P2 (commercial feed + black cumin 4% + heat stress 34-35); P3 (commercial feed + black cumin 6% + heat stress 34-35 ); P4 (commercial feed + black cumin 8% + heat stress 34- 35 ). Feeding was given twice a day at 07.00 WIB and 17.00 WIB ad libitum. Heat stress was given from 10.00 - 15.00 WIB every day for 14 days. The chicken breast and thigh meat were collected on day 29 for analysis. The statistical analysis showed that feed supplement containing black cumin had no effect (P0.05) on the pH value, drip loss, texture, protein content, and structure of broiler meat given exposure to heat stress, but had effect (P0.05) on the organoleptic colour, smell and texture, and cholesterol level of broiler meat. Based on these results, it can be concluded that feeding with 4%, 6% and 8% black cumin did not change the pH, drip loss, texture value as well as protein and water content of broiler meat given heat stress, but produced better colour and aroma. The administration of 4% cumin can reduce cholesterol levels of broiler meat exposed to heat stress.